1992
DOI: 10.1161/01.cir.86.5.1383
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound evaluation of the effect of rotational atherectomy in obstructive atherosclerotic coronary artery disease.

Abstract: Rotational atherectomy causes atheroablation with only moderate evidence of barotrauma in heavily calcified arteries, even after adjunct balloon angioplasty. The lumen is cylindrical, especially in areas of calcified plaque, and somewhat larger than the largest burr tip used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(47 citation statements)
references
References 18 publications
0
46
0
1
Order By: Relevance
“…RA can facilitate smooth stent delivery and stent expansion through lesion modification. [4][5][6] However, the clinical outcomes after implanting a baremetal stent (BMS) following RA have not been satisfactory. [7][8][9] Drug-eluting stents (DES) have dramatically reduced the rate of revascularization compared with BMS.…”
mentioning
confidence: 99%
“…RA can facilitate smooth stent delivery and stent expansion through lesion modification. [4][5][6] However, the clinical outcomes after implanting a baremetal stent (BMS) following RA have not been satisfactory. [7][8][9] Drug-eluting stents (DES) have dramatically reduced the rate of revascularization compared with BMS.…”
mentioning
confidence: 99%
“…revious studies have reported the frequency and clinical significance of coronary artery calcification [1][2][3][4][5][6][7][8][9][10][11][12][13][14] ; however, no prior study has described the frequency, pattern, distribution, and clinical correlates of calcium in saphenous vein grafts (SVGs). Therefore, the purpose of this study was (1) to use intravascular ultrasound (IVUS) to determine the arc, length, location, orientation, and distribution of SVG calcification; (2) to compare these IVUS results with angiographic findings; and (3) to correlate SVG calcification with clinical characteristics.…”
mentioning
confidence: 99%
“…[1][2][3][4] Studies using sequential IVUS imaging, before and after RA, have shown significant increases in minor and major lumen diameters, 2 a significant increase in lumen CSA, no significant change in EEM CSA, 1,2 and a significant decrease in plaque plus media CSA. 1,3 Dussaillant et al reported that the lumen volume significantly increased after RA as a result of a significant decrease in plaque plus media volume, with no change in total EEM volume.…”
Section: Discussionmentioning
confidence: 99%